2022
DOI: 10.2147/jir.s377301
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of Inflammatory Endotypes and Clinical Characteristics in Chronic Rhinosinusitis with Nasal Polyps

Abstract: Objective Chronic rhinosinusitis with nasal polyps (CRSwNP) is mainly characterised by type 1 (T1), type 2 (T2) and type 3 (T3) inflammatory endotypes. However, correlations between inflammatory endotypes and clinical features in CRSwNP have not been demonstrated sufficiently. This study aimed to determine the endotype-phenotype associations in CRSwNP. Methods Clinical data of 31 control subjects and 106 CRSwNP patients were analysed. Interferon (IFN)-γ (T1), Charcot-Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Although endotyping has proven to be pivotal in the management of chronic inflammation of CRSwNP, the actual clinical presentation may comprise a spectrum with overlapped inflammatory responses. Indeed, Hao et al [72] found that IL-17A production correlated in turn with IFN-γ production, which highlights the existence of a synergistic effect between the T1 and T3 inflammatory response in the pathogenesis of certain patients with CRSwNP.…”
Section: Interleukin-17 (Il-17)mentioning
confidence: 99%
“…Although endotyping has proven to be pivotal in the management of chronic inflammation of CRSwNP, the actual clinical presentation may comprise a spectrum with overlapped inflammatory responses. Indeed, Hao et al [72] found that IL-17A production correlated in turn with IFN-γ production, which highlights the existence of a synergistic effect between the T1 and T3 inflammatory response in the pathogenesis of certain patients with CRSwNP.…”
Section: Interleukin-17 (Il-17)mentioning
confidence: 99%
“…13 However, recent findings in research point out that CRS may be a much more complex disease with many different factors contributing to its development. 14,15 Studies examining the contribution of the nasal microvasculature to CRS pathophysiology generally focus more on blood vessels than on LVs. 16 However, one study suggested that the occurrence of nasal polyps is connected to a lower lymphatic vessel density, 17 and currently there is also speculation about the participation of the micro lymphvasculature in non-type 2 inflammatory endotypes.…”
Section: Introductionmentioning
confidence: 99%